Evolution of the stable carbon isotope composition of atmospheric CO2 over the last glacial cycle. (24th March 2016) - Eggleston, S.; Schmitt, J.; Bereiter, B.; Schneider, R.; Fischer, H.
Abstract: We present new δ 13 C measurements of atmospheric CO2 covering the last glacial/interglacial cycle, complementing previous records covering Terminations I and II. Most prominent in the new record is a significant depletion in δ 13 C(atm) of 0.5‰ occurring during marine isotope stage (MIS) 4, followed by an enrichment of the same magnitude at the beginning of MIS 3. Such a significant excursion in the record is otherwise only observed at glacial terminations, suggesting that similar processes were at play, such as changing sea surface temperatures, changes in marine biological export in the Southern Ocean (SO) due to variations in aeolian iron fluxes, changes in the Atlantic meridional overturning circulation, upwelling of deep water in the SO, and long‐term trends in terrestrial carbon storage. Based on previous modeling studies, we propose constraints on some of these processes during specific time intervals. The decrease in δ 13 C(atm) at the end of MIS 4 starting approximately 64 kyr B.P. was accompanied by increasing [CO2 ]. This period is also marked by a decrease in aeolian iron flux to the SO, followed by an increase in SO upwelling during Heinrich event 6, indicating that it is likely that a large amount of δ 13 C‐depleted carbon was transferred to the deep oceans previously, i.e., at the onset of MIS 4. Apart from the upwelling event at the end of MIS 4 (and potentially smaller events during Heinrich events in MIS 3), upwelling of deep water in the SO remained reduced until the last glacial termination, whereupon a second pulse of isotopically light carbon was released into the atmosphere. Key Points: First complete record of atmospheric δ 13 C of CO2 155 kyr B.P. to present Quantification of the effect of the marine biological soft‐tissue pump on [CO2 ] at the MIS 5‐4‐3 transitions Transfer of isotopically light C to the deep ocean at the onset of MIS 4